Biodiversity of thermophilic microflora of oil-bearing waters of the Akingen field (Experimental biology, 2019)
The article provides the quantitative and qualitative microbiological characteristics of the reservoir waters of the Akingen deposit. The purpose of this work is to study the biodiversity of thermophilic microflora of formation waters. Microorganisms of petroleum waters, adapted to the extreme conditions of petroleum plasters, are promising targets for the development of microbiological methods of enhanced oil recovery based on the ability of microorganisms to displace oil. The work used traditional microbiological methods for the study of microorganisms. During the study, 14 aerobic and anaerobic thermophilic cultures of microorganisms with related affiliation were identified and identified; therefore, 12 cultures of microorganisms were classified as Pseudomonas (T1, T2, T3, T4, T5, T6, D1, D2, D4, D5, D6, D7 ), 1 as a representative of the genus Bacillus (D8) and 1 - sulfate-reducing microorganisms (D9). It has been established that aerobic microorganisms of these reservoir waters dominate over anaerobic microorganisms and constitute 96.1x108 CFU/ml, whereas the number of anaerobic microorganisms is 14x103 CFU/ml. It was revealed that the following groups of microorganisms are contained in petroleum waters: pseudomonads, bacilli, and sulphate-reducing microorganisms. It was shown that the oil in the Akingen field has a pH of 6.34. Isolated microorganisms require further study of target properties for the development of biotechnological methods of enhanced oil recovery.Keywords: "Akingen" deposits, oil-bearing water, thermophiles, “oil-negative” microorganisms, cultural properties.